CALCULATION OF EUTECTOID CONVERSIONS IN CASTINGS AT FOUNDING BY MEANS OF CONTINUOUSLY-CYCLIC FOUNDING BY FROSTING - A. M. Bodyako; P. I. Zimonin; I. A. Melnikov; A. A. Suponev (Литьë и металлургия)
The dependencies for calculation of the eutectoid inversions time in castings of different dimension-type at cooling in the air are received.